Online game addiction in adolescent: What should school counselor do? - Eryzal Novrialdy; Rozi Atyarizal (Jurnal Konseling dan Pendidikan)
Online game addiction in adolescents has become one of the problems that get a lot of public attention. Increasingly developing of technology, easy access and lack of comprehension of adolescents towards the dangers of online game addiction are some of the factors that easily make adolescent become addicted to online games. Online game addiction is a play activity that is carried out excessively and interferes with daily life. Online game addiction that occur in adolescents can have an impact on various aspects of life, such as health aspects, psychological aspects, academic aspects, social aspects and financial aspects. This problem must be prevented, one of them is by school counselor. Various prevention efforts can be carried out by school counselor, include: providing seminars, socialization and online game addiction hazard modules.